The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3352/jeehp.2017.14.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an undergraduate occupational health program in Iran based on alumni perceptions: a structural equation model

Abstract: PurposeEvaluating educational programs can improve the quality of education. The present study evaluated the undergraduate occupational health program at the Semnan University of Medical Sciences in Semnan, Iran, with a focus on the associations between alumni perceptions of the learning environment and the outcomes of the occupational health program.MethodsA cross-sectional questionnaire survey was conducted among alumni of the undergraduate occupational health program. We asked alumni to rate their perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The purpose of this study is to examine if teacher performance affects OPJBL and ESP learning outcomes to better understand the role of teacher performance in ensuring course implementation success and improving learning outcomes. Prior research has also found that instructional resources are essential influences in ensuring course implementation success (Cobb et al, 2015;Mehralizadeh et al, 2017). The term 'technology resource' is used in this study to refer to all items needed to implement the program.…”
Section: The Studymentioning
confidence: 99%
“…The purpose of this study is to examine if teacher performance affects OPJBL and ESP learning outcomes to better understand the role of teacher performance in ensuring course implementation success and improving learning outcomes. Prior research has also found that instructional resources are essential influences in ensuring course implementation success (Cobb et al, 2015;Mehralizadeh et al, 2017). The term 'technology resource' is used in this study to refer to all items needed to implement the program.…”
Section: The Studymentioning
confidence: 99%
“…Tugas proyek dapat melatih kreativitas, komitmen, dan kemampuan menulis mahasiswa. Mehralizadeh, et. al.…”
Section: Hasil Dan Pembahasanunclassified
“…Tourism curriculum may include, courses related to the Tourism management, educational and training environments, educational materials and information, research projects, field trips, laboratory courses etc. (Mehralizadeh, Dehdashti, & Kashani, 2017).…”
Section: Curriculummentioning
confidence: 99%
“…Most evaluation studies in academic environments have focused on the curriculum, teaching and learning methods, student-faculty interactions, and student outcomes (Mehralizadeh et al, 2017) In a previous study, researchers assessed the quality of faculty members according to achievements in education, training, research, and scholarship (Arimoto et al, 2012). Previous research reported that faculty members who focused on improving the overall quality of their teaching could enhance the students' level of motivation and higher-order thinking skills (Dehdashti et al, 2013).…”
Section: The Relationship Between Tourism Education and Learning Outcmentioning
confidence: 99%